2022
DOI: 10.3390/life12030328
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula pedunculata (Mill.) Cav. Aqueous Extract Antibacterial Activity Improved by the Addition of Salvia rosmarinus Spenn., Salvia lavandulifolia Vahl and Origanum compactum Benth

Abstract: Lavender aqueous extracts are widely used in the Moroccan traditional medicine for their antibacterial properties. However, previous research have generally focused on investigating the antibacterial activity of lavender essential oils. The aim of this study is to evaluate the antibacterial activity of the Moroccan Lavandula pedunculata (Mill.) Cav. aqueous extract, alone, as well as in combination with extracts of other plant species known for their antibacterial activity: Salvia rosmarinus Spenn., Salvia lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…Our results agree with those of Salima Boutahiri et al, having identified rosmarinic acid, apigenin, luteolin, myricetin, herniarin, caffeic acid, protocatechuic acid, coumarin, cinnamic acid, vanillic acid, gallic acid, and chlorogenic acid in the aqueous extract of S. lavandulifolia leaves [ 17 ]. Salvador Cafligueral et al revealed the presence of apigenin, luteolin, rosmarinic acid, quercetin-3-O-β-D-glucoside, luteolin-7-O-β-D-glucoside, luteolin-4′-O-glucoronide, luteolin-7-O-rutinoside, and other compounds such as nepetin and 5-Hydroxy-7, 4′-dimethoxyflavone in the soluble fraction of petroleum ether and chloroform extracts from the leaves of S. lavandulifolia [ 45 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results agree with those of Salima Boutahiri et al, having identified rosmarinic acid, apigenin, luteolin, myricetin, herniarin, caffeic acid, protocatechuic acid, coumarin, cinnamic acid, vanillic acid, gallic acid, and chlorogenic acid in the aqueous extract of S. lavandulifolia leaves [ 17 ]. Salvador Cafligueral et al revealed the presence of apigenin, luteolin, rosmarinic acid, quercetin-3-O-β-D-glucoside, luteolin-7-O-β-D-glucoside, luteolin-4′-O-glucoronide, luteolin-7-O-rutinoside, and other compounds such as nepetin and 5-Hydroxy-7, 4′-dimethoxyflavone in the soluble fraction of petroleum ether and chloroform extracts from the leaves of S. lavandulifolia [ 45 ].…”
Section: Resultssupporting
confidence: 93%
“…Our results are almost identical to those found by Boutahiri et al (2021) in terms of total polyphenol content. They found that the aqueous extract of S. lavandulifolia obtained by decoction contains 252.67 ± 5.40 mg EAG/g DE [ 17 ]. Polyphenols are considered the most abundant group of secondary metabolites in plants, through which they defend themselves against predators and intrusions [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference could be justified by the degree of polarity of each solvent to drive the phenolic compounds [ 84 ]. These phenolic compounds are secondary metabolites that have been extensively researched in a variety of medicinal plants, fruits, and vegetables [ 42 , 85 ]. They have antioxidant, antibacterial, and carbohydrase inhibitor properties.…”
Section: Resultsmentioning
confidence: 99%